2007
DOI: 10.1016/j.neuron.2006.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Phospho-Dependent Functional Modulation of GABAB Receptors by the Metabolic Sensor AMP-Dependent Protein Kinase

Abstract: GABA(B) receptors are heterodimeric G protein-coupled receptors composed of R1 and R2 subunits that mediate slow synaptic inhibition in the brain by activating inwardly rectifying K(+) channels (GIRKs) and inhibiting Ca(2+) channels. We demonstrate here that GABA(B) receptors are intimately associated with 5'AMP-dependent protein kinase (AMPK). AMPK acts as a metabolic sensor that is potently activated by increases in 5'AMP concentration that are caused by enhanced metabolic activity, anoxia, or ischemia. AMPK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
163
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 166 publications
(168 citation statements)
references
References 40 publications
5
163
0
Order By: Relevance
“…S1E). To confirm the in vivo ablation of the catalytic activity of AMPK, we used phospho-specific antibodies detecting two previously characterized AMPK protein substrates: serine 783 of the GABA B receptor 2 (19) and retinoblastoma (Rb) protein on serines 807 and 811 (10). Phosphorylation of both of these proteins is abolished in the P3 cortex of AMPKα-DcKO compared with control mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S1E). To confirm the in vivo ablation of the catalytic activity of AMPK, we used phospho-specific antibodies detecting two previously characterized AMPK protein substrates: serine 783 of the GABA B receptor 2 (19) and retinoblastoma (Rb) protein on serines 807 and 811 (10). Phosphorylation of both of these proteins is abolished in the P3 cortex of AMPKα-DcKO compared with control mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that lithium inhibits PP2A activity [20,21], which has been shown to regulate phosphorylation of AMPK [31]. The observed effects of lithium on AMPK may also be related to the neuroprotective effects of lithium because AMPK activation is connected to cell survival in several systems [32][33][34]. Immunohistochemical data suggested that the subcellular localization of phospho-AMPK in "ethanol + lithium" group is different from that in control and lithium groups.…”
Section: Discussionmentioning
confidence: 99%
“…Patch Clamp Electrophysiology-Membrane currents were recorded, using whole cell patch clamp, from single GIRK cells as described previously (24). Patch pipettes (3-5 M⍀) were filled with a solution containing (mM): 120 KCl, 2 MgCl 2 , 11 EGTA, 30 KOH, 10 HEPES, 1 CaCl 2 , 1 GTP, 2 ATP, 14 creatine phosphate, pH 7.0.…”
Section: Gaba B Receptor Containing the Btx-binding Site-com-mentioning
confidence: 99%
“…To construct GABA concentration-response relationships, the current (I) was measured in the presence of each concentration of GABA applied at 3-min intervals as described previously (24). The currents were normalized to the maximum GABA response (I max ) and the concentration response relationship fitted with the Hill equation (24).…”
Section: Gaba B Receptor Containing the Btx-binding Site-com-mentioning
confidence: 99%
See 1 more Smart Citation